Chondrogenesis of human mesenchymal stem cells by local transforming growth factor-beta delivery in a biphasic resorbable carrier - Dickhut, Andrea; Dexheimer, Verena; Martin, Katja; Lauinger, Rebekka; Heisel, Jens Christian; Richter, Wiltrud (Tissue engineering, 2010)
Little is known about the potential of growth factor-augmented biphasic implants composed of a gel and a solid scaffold to enhance chondrogenesis of mesenchymal stem cells (MSCs). We analyzed whether a collagen type I/III carrier and fibrin glue (FG) combined to a biphasic construct support in vitro chondrogenesis of MSCs and allow for local release of bioactive transforming growth factor-beta1 (TGF-β1). Further, a possible advantage of partial autologous fibrin glue (PAF) over commercial FG was assessed. Collagen carriers seeded with 5 × 105 human MSCs with or without FG, PAF, or TGF-β1-upgraded FG were cultured for 6 weeks in chondrogenic medium with or without TGF-β1. Pellets with or without FG/PAF served as controls. FG and collagen carriers allowed strong upregulation of COL2A1, AGC, and COL10A1 mRNA, deposition of collagen-type II, and mediated a significantly higher proteoglycan content compared with biomaterial-free pellets. Collagen-carrier groups contained significantly more proteoglycan than FG and PAF pellets, whereas biphasic PAF-carrier constructs were inferior to FG-carrier constructs. Upgrading of biphasic FG-carrier constructs with 50 ng TGF-β1/construct mediated chondrogenesis as successfully as supply of TGF-β1 via the medium. In conclusion, the biphasic carrier constructs showed a high biofunctionality by continuous form stability with improved chondrogenesis and long-term local supply of bioactive TGF-β1 which may be useful to enhance matrix-assisted repair strategies for damaged cartilage.
Online veröffentlicht: 8 October, 2009
Gesehen am 14.02.2024